IMPLEMENTASI PENDEKATAN STEAM BERBASIS MODEL PjBL MELALUI PEMBELAJARAN ONLINE DALAM MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS DAN KREATIVITAS SISWA PADA MATERI PENCEMARAN LINGKUNGAN DI KELAS X SMA NEGERI 1 DUKUPUNTANG - Jumerah, Jujum; Hindriana, Anna Fitri (Program Studi Pendidikan Biologi, Sekolah Pascasarjana Universitas Kuningan, 2022)
The aim of study is to improve students’ creativity and critical thinking skills after implementing STEAM approach based on project based learning with online. The research method used a quasi-experimental design with a pretest-posttest control group. The sample used with purposively was 20 students, which were divided into experimental and control groups. Data was taken by using critical thinking skills test, questionnaires, observation, and documentation. The data analysis technique used descriptive analysis and the average difference test.The conclusions of the study was: (1) There is a significant average difference in critical thinking skills between the experimental class and the control class after implementing the STEAM approach with the class that does not use the STEAM approach on Environmental Pollution Material in Class X SMA Negeri 1 Dukupuntang as evidenced by the value probability (p) 0.015 <0.05. (2) Student creativity in the experimental class on fluency indicators reaches 82.5%, flexibility indicators 90%, originality indicators 90% and elaboration indicators 86.88%, with an overall average score of 86.88% which is included in the very good category.